Construction of spatial models in the monitoring system based on observation data on the ground - Білецький, А. Я.; Приставка, П. О. (Proceedings of National Aviation University (archive), 2021)
The information technology with the use of the regularization of data and local polynomial splines to construct realistic distribution models man-made pollution. An example of application of technology according to the data in the monitoring area of ​​the tailings storage of radioactive waste is given